2017
DOI: 10.5530/ijper.51.4s.98
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Herbal OTC Products and Dietary Supplements by Patients Receiving Chemotherapy: Survey-Based Study

Abstract: Context: Among cancer patients receiving chemotherapy, there is a growing trend to use self-medication. Many of them take preparations sold over the counter (OTC) and dietary supplements containing plant raw materials. Aims: The aim of this study is to evaluate the herbal OTC drug and dietary supplement usage among patients treated on the chemotherapy ward. Settings and Design: An anonymous survey was conducted among 92 patients of the chemotherapy ward of the Lower Silesian Oncology Center in Wroclaw (Poland)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Most of the times patients are willing to undergo TSM [ 16 ] with the Physician of respective systems of medicine. The lack of availability of Physicians of such traditional system of medicines or unawareness about the availability among patients as well as primary service providers in healthcare system; make patients search and opt for over the counter (OTC) products [ 17 ]. The OTC products at times mention tall claims, which misguides patients and by the time they return to Oncology experts, the upstaging of cancer might already has occurred.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the times patients are willing to undergo TSM [ 16 ] with the Physician of respective systems of medicine. The lack of availability of Physicians of such traditional system of medicines or unawareness about the availability among patients as well as primary service providers in healthcare system; make patients search and opt for over the counter (OTC) products [ 17 ]. The OTC products at times mention tall claims, which misguides patients and by the time they return to Oncology experts, the upstaging of cancer might already has occurred.…”
Section: Discussionmentioning
confidence: 99%
“…from red clover, black bedbug, hops or soybeans. Due to their vegetable, natural origin and availability without a prescription, these preparations are widely considered safe, which may result in their use by a patient without the knowledge and control of a doctor [39,40,41]. Phytoestrogens, in particular flavonoid genistein, are the best studied group of xenoestrogens in terms of interaction with drugs used in the treatment of hormone-dependent breast cancer.…”
Section: Description Of the State Of Knowledgementioning
confidence: 99%
“…Interestingly, compared to other nationalities, Poles seem to be more often aware that using dietary supplements may have an impact on the results of medical laboratory tests and consider it proper to inform lab personnel about their consumed products [9]. Unfortunately, however, still almost one-third of patients who participated in a survey carried out in one of Polish oncology centres indicated that they had not informed their physicians about supplements they were using concurrently [10]. This approach may result from a growing belief among Poles that supplements are not medicines or pharmaceuticals but rather natural products that enhance a regular healthy diet.…”
Section: Introductionmentioning
confidence: 99%